A novel long noncoding RNA Lnc‐HC binds hnRNPA2B1 to regulate expressions of Cyp7a1 and Abca1 in hepatocytic cholesterol metabolism. Issue 1 (22nd January 2016) - Lan, Xi; Yan, Jidong; Ren, Juan; Zhong, Bo; Li, Jing; Li, Yue; Liu, Li; Yi, Jing; Sun, Qingzhu; Yang, Xudong; Sun, Jian; Meng, Liesu; et al.
Abstract : Cholesterol metabolism disorder in hepatocytes predicts a higher risk of metabolic syndrome (MetS). Long noncoding RNAs (lncRNAs) have emerged as critical players in cellular cholesterol metabolism, but their functions are not systematically clarified. Here, we have identified a novel lncRNA named lnc‐HC negatively regulating cholesterol metabolism within hepatocytes through physical interaction with hnRNPA2B1. By further binding to the target messenger RNA of Cyp7a1 or Abca1, the lnc‐HC ‐hnRNPA2B1 complex decreases expressions of the two genes that are implicated in cellular cholesterol excretion. lnc‐HC knockdown can strongly recover the cholesterol disorder in vivo . In the upstream pathway, lnc‐HC is up‐regulated by high cholesterol by the transcription activator, CCAAT/enhancer‐binding protein beta. Conclusion: These findings suggest a subtle feed‐forward regulation of lnc‐HC in cholesterol metabolism and define a novel line of evidence by which lncRNAs modulate the metabolic system at the post‐transcriptional level. (Hepatology 2016;64:58‐72)